2020
DOI: 10.1038/s41467-020-15835-3
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin expression and the humoral immune response is regulated by the non-canonical poly(A) polymerase TENT5C

Abstract: TENT5C is a non-canonical cytoplasmic poly(A) polymerase highly expressed by activated B cells to suppress their proliferation. Here we measure the global distribution of poly(A) tail lengths in responsive B cells using a Nanopore direct RNA-sequencing approach, showing that TENT5C polyadenylates immunoglobulin mRNAs regulating their half-life and consequently steady-state levels. TENT5C is upregulated in differentiating plasma cells by innate signaling. Compared with wild-type, Tent5c −/− mice produce fewer a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(91 citation statements)
references
References 60 publications
5
86
0
Order By: Relevance
“…Total RNA was extracted from wild-type and urt1-1 flowers using Tri-Reagent (Molecular Research Center) following the manufacturer’s recommendations. Capped mRNAs were enriched using GST-eIF4E-K119A protein 70 . Nanopore direct-RNA libraries were prepared from 5 µg of Arabidopsis cap-enriched mRNA with 150 ng of yeast poly(A)-enriched RNA using Direct RNA Sequencing Kit (ONT, SQK-RNA002) 71 .…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted from wild-type and urt1-1 flowers using Tri-Reagent (Molecular Research Center) following the manufacturer’s recommendations. Capped mRNAs were enriched using GST-eIF4E-K119A protein 70 . Nanopore direct-RNA libraries were prepared from 5 µg of Arabidopsis cap-enriched mRNA with 150 ng of yeast poly(A)-enriched RNA using Direct RNA Sequencing Kit (ONT, SQK-RNA002) 71 .…”
Section: Methodsmentioning
confidence: 99%
“…TENT5A is a paralog of the cytoplasmic poly(A) polymerase TENT5C, an onco-suppressor in multiple myeloma (Mroczek et al, 2017). Importantly, TENT5C increases the expression of immunoglobulins and other secreted proteins in the B cell lineage by stabilizing their mRNAs (Bilska et al, 2020;Mroczek et al, 2017). This suggests that, by analogy, TENT5A may similarly regulate the expression of secreted proteins in osteoblasts, presumably involved in bone formation, dysfunction of which could lead to a bone-related phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…It appears that TENT5C plays a broad role in B cell biology. Cytoplasmic polyadenylation by TENT5C was recently shown to stimulate the humoral immune response (Bilska et al, 2020; Herrero et al, 2020). A global analysis of poly(A) tail distribution by nanopore direct RNA sequencing revealed that mRNAs that encode Igs carry shorter poly(A) tails and have lower steady‐state levels in B cells that are isolated from TENT5C knockout mice compared with wild‐type mice (Bilska et al, 2020).…”
Section: Noncanonical Polyadenylationmentioning
confidence: 99%
“…Cytoplasmic polyadenylation by TENT5C was recently shown to stimulate the humoral immune response (Bilska et al, 2020; Herrero et al, 2020). A global analysis of poly(A) tail distribution by nanopore direct RNA sequencing revealed that mRNAs that encode Igs carry shorter poly(A) tails and have lower steady‐state levels in B cells that are isolated from TENT5C knockout mice compared with wild‐type mice (Bilska et al, 2020). TENT5C ‐deficient B cells exhibit a reduction of Ig mRNA and protein abundance and secrete fewer antibodies (Bilska et al, 2020; Herrero et al, 2020).…”
Section: Noncanonical Polyadenylationmentioning
confidence: 99%